Pervaporation dehydration of bio-fuel (n-butanol) by dry thermal treatment membrane - Soheila Manshad; Arun M Isloor; Mohd Ghazali Mohd Nawawi; Inamuddin; Imran Khan; Hadi M Marwani (Materials Research Express, 2020)
In the present investigation, laboratory synthesized graphene oxide (GO) as a nano-filler was used in polyetherimide (PEI) flat-sheet membranes (PM). The PEI flat-sheet membrane was fabricated through a dry-thermal treatment (DTT) method. The effects of fabrication method were investigated on polyetherimide-GO membrane prepared by dry-thermal treatment (PMDTT). The morphological structure was investigated via different characterization; Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), contact angle measurement and Raman spectra. The results indicated that, the hybrid PMDTT membrane displayed reasonably better pervaporation separation performance in comparison to neat PMDTT membranes. The concentrations of water at the permeate side of hybrid and neat PMDTT membrane were 99.3 and 90.9 wt.%, respectively. Hybrid membranes showed a 78.3% enhanced permeation rate. Enhancement of pervaporation property of hybrid PMDTT membrane could be ascribed mainly due to the presence of graphene oxide in the dense top layer. Overall, the blending of graphene oxide in hybrid PMDTT membranes could be a promising approach for enhancing the pervaporation properties of the membranes.